2013
DOI: 10.1155/2013/404361
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Droplet Vaporization in Biology and Medicine

Abstract: This paper reviews the literature regarding the use of acoustic droplet vaporization (ADV) in clinical applications of imaging, embolic therapy, and therapeutic delivery. ADV is a physical process in which the pressure waves of ultrasound induce a phase transition that causes superheated liquid nanodroplets to form gas bubbles. The bubbles provide ultrasonic imaging contrast and other functions. ADV of perfluoropentane was used extensively in imaging for preclinical trials in the 1990s, but its use declined ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 85 publications
1
75
0
4
Order By: Relevance
“…This circulation of the dynamic system has been reported by Sheeran et al [45] and observed with PFP and PFH nanoparticle droplets in water at 25 °C and 37 °C [46].…”
Section: Bubble Growthsupporting
confidence: 81%
See 2 more Smart Citations
“…This circulation of the dynamic system has been reported by Sheeran et al [45] and observed with PFP and PFH nanoparticle droplets in water at 25 °C and 37 °C [46].…”
Section: Bubble Growthsupporting
confidence: 81%
“…The gas bubble nucleated will be continuous to grow without the limitation in terms of the heat after the increasing internal pressure of droplets ultimately exceeds the vapor pressure in the ultrasonic field, because the heat is adequate to converted into the energy demanded for satisfying the formation of the gas phase [46]. This circulation of the dynamic system has been reported by Sheeran et al [45] and observed with PFP and PFH nanoparticle droplets in water at 25 °C and 37 °C [46].…”
Section: Bubble Growthmentioning
confidence: 68%
See 1 more Smart Citation
“…This introductory chapter is devoted broadly to the topic of theranostics and the role of functional nanometer-sized agents in personalized medicine [1,50,59,[67][68][69][70][71][72][73][74]. Over the past 2 decades, the field has gained a tremendous boost with high impending for translation.…”
Section: Resultsmentioning
confidence: 99%
“…As PDUS is dependent on density and size of the imaged particles, the signal detected reflected the size increase of the NBs associated with the vaporization of the perfluoropentane core, due to ADV phenomenon. ADV is a physical process in which the pressure waves of US induce a phase transition that cause liquid nanodroplets to form gas bubbles [41]. Furthermore, the nanodroplets to nanobubble conversion was also observed by optical microscopy analysis.…”
Section: Page 14 Of 27mentioning
confidence: 97%